The Role of Foreign Firm Characteristics, Absorptive Capacity and the Institutional Framework for FDI Spillovers - Thomas Farole; Deborah Winkler (Journal of Banking and Financial Economics)
A vast set of empirical evidence has been amassed over the past decade on the existence and direction of foreign direct investment (FDI)-generated horizontal and vertical spillovers. Overall, the results are mixed, and suggest that the theoretical postulated spillover effects often do not automatically materialize just because a country is able to attract FDI in the first place. As a result, more and more research has been devoted to understanding the various conditions that may explain these mixed results. Using a cross-section of more than 25,000 domestic manufacturing firms in 78 low-and middle-income countries from the World Bank’s Enterprise Surveys Indicator Database we assess how mediating factors influence productivity spillovers to domestic firms from FDI. We differentiate between three types of mediating factors: (i) a foreign investor’s spillover potential, (ii) a domestic firm’s absorptive capacity, and (iii) a country’s institutional framework. We find that all three affect the extent and direction of FDI spillovers on domestic firm productivity. Moreover, we find that the impact of mediating factors depends on domestic firms’ productivity and the structure of foreign ownership.